Discovery of sound in the sea: an online resource - Vigness-Raposa, K.; Scowcroft, G.; Miller, J.; Ketten, Darlene (Springer New York LLC, 2012)
The scientific community and the general public have become increasingly aware of and concerned about underwater sound. In addition, abstract physical science concepts can be challenging to understand. As the interest in underwater sound and its potential effects on the marine environment increases, there is a growing need for resources on the fundamental concepts of underwater sound. The Discovery of Sound in the Sea (DOSITS) Web site (http://www.dosits.org) has been designed to provide comprehensive scientific information on underwater sound at a level appropriate for the general public and for educational and media professionals (Vigness-Raposa et al. 2008). The DOSITS Web site introduces the physical science of underwater sound and how people and animals use sound to accomplish various tasks in three science sections, three resources sections, and three galleries. DOSITS was recently redesigned to include an interactive front page, an interactive Audio Gallery, and a redesigned Scientist Gallery.